2001
DOI: 10.1128/jcm.39.9.3321-3325.2001
|View full text |Cite
|
Sign up to set email alerts
|

Six-Year Study of the Incidence of Herpes in Genital and Nongenital Cultures in a Central Kentucky Medical Center Patient Population

Abstract: Herpes infections are among the most common sexually transmitted diseases and are the most common cause of genital ulcer disease in the United States. This study addresses the changing distribution of herpes simplex virus type 1 (HSV-1) and HSV-2 in patients presenting for evaluation of herpetic infections. Viral culture results from the University of Kentucky Clinical Microbiology Laboratory were reviewed for a 6-year period (1994 through 1999). Data were collected on patient sex, site of culture, and culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
1
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(38 citation statements)
references
References 36 publications
(46 reference statements)
1
34
1
2
Order By: Relevance
“…The increase in genital HSV-1 initially was observed in Europe, and more recently in the USA and Australia. 15,21,22 The increase is thought to be the result of both less frequent acquisition of HSV-1 in childhood and more frequent oral-genital contact at the initiation of sexual activity. 35,36 Not surprisingly, the increase in genital HSV-1 infection has resulted in an increase in neonatal HSV-1 in proportions that meet or exceed that caused by HSV-2.…”
Section: Increasing Importance Of Neonatal Hsv-1mentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in genital HSV-1 initially was observed in Europe, and more recently in the USA and Australia. 15,21,22 The increase is thought to be the result of both less frequent acquisition of HSV-1 in childhood and more frequent oral-genital contact at the initiation of sexual activity. 35,36 Not surprisingly, the increase in genital HSV-1 infection has resulted in an increase in neonatal HSV-1 in proportions that meet or exceed that caused by HSV-2.…”
Section: Increasing Importance Of Neonatal Hsv-1mentioning
confidence: 99%
“…2 HSV-1 has emerged as a major cause of genital herpes among college-age populations, in which up to 80% of new cases of genital HSV were caused by HSV-1. [14][15][16] Epidemiological studies suggest that oral genital contact is the major risk factor for the acquisition of genital HSV-1. 17 Similar findings have been reported worldwide.…”
Section: Epidemiology Of Genital Herpesmentioning
confidence: 99%
“…7 In Norway, HSV-1 has overtaken HSV-2 as the major cause of genital infection in females and the young, 8 and a Swedish study has shown the regular occurrence of both virus types in ''below the neck'' infections. 9 In the United States, increasing proportions of genital HSV-1 affecting mainly females 10 and college students 11 have been reported. Similar proportions of genital and oropharyngeal HSV-1 infections have also been reported in sexually active HSV-2 seronegative adults.…”
mentioning
confidence: 99%
“…HSV-1 also accounts for 10 to 15% of all genital herpetic infections (3,6,11). The proportion of genital infections with HSV-1 is reportedly even higher in some locations (4,10,13).…”
mentioning
confidence: 99%